Tax justice and tax law : understanding unfairness in tax systems - De Cogan, Dominic; Harris, Peter (Editor of Tax justice and tax law) (London [England] : Hart Publishing, 2020)
"Most people would agree that tax systems ought to be 'just', and perhaps a great deal more just than they are at present. What is more difficult is to agree on what tax justice is. This book considers a range of different approaches to, and ideas about the nature of tax justice and covers areas such as: - imbalances in international tax arrangements that deprive developing countries of revenues from natural resources and allow wealthy taxpayers to use tax havens; - protests against governments and large business; - attempts to influence policy through more technical means such as the OECD's Base Erosion and Profits Shifting project; - interpersonal matters, such as the ways in which tax systems disadvantage women and minorities; - the application of wider philosophical or economic theories to tax systems. The purpose of the book is not to iron out these underlying differences into a grand theory, but rather to gain a more precise understanding of how and why we disagree about tax justice. In doing so the editors are assisted by a stellar cast of contributors from four continents, with a wide variety of views and experiences but a common interest in this central question of how to agree and disagree about tax justice. This is, of course, not only an intellectual exercise but also a necessary precursor to achieving real-world change"--
Mapping tax justice arguments / de Cogan -- A principle of 'natural justice' : Sir William Petty's Treatise of Taxes and contributions and the 'Royal Absolutist' Case for excise / Matthew Ward -- Balancing conflicting conceptions of justice in taxation / Sonja Dusarduijn and Hans Gribnau -- (Un)fairness as an irritant to the legal system : the case of two legislatures and more multinational enterprises / Emer Hunt -- Taxing for social justice or for growth? / êAsa Gunnarsson -- A brief theory of taxation and framework public goods / Darien Shanske -- A critical analysis of how formal and informal citizenships influence justice between mobile taxpayers / Yvette Lind -- Immigration, emigration, fungible labour and the retreat from progressive taxation / Henry Ordower -- What may we expect of a theory of international tax justice? / Dirk Broekhuijsen and Henk Vording -- Re-imagining tax justice in a globalised world / Tsilly Dagan -- Between legitimacy and justice in international tax policy / Ivan Ozai -- Tax justice in the post-BEPS Era : enhanced cooperation among tax authorities and the protection of taxpayer rights in the EU / Christiana HJI Panayi and Katerina Perrou -- Tax justice and older people : an examination through the lens of critical tax theory / Jane Frecknall-Hughes, Nashid Monir, Barbara Summers and Simon James -- Tax tribunals and justice for litigants in person / Richard Thomas -- New wave technologies and tax justice / Benjamin Walker.
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Taxation -- Law and legislation; Tax administration and procedure; Fiscal policy; Taxation & duties law; Electronic books